2021
DOI: 10.1007/s00420-021-01665-3
|View full text |Cite
|
Sign up to set email alerts
|

Is N95 face mask linked to dizziness and headache?

Abstract: Objectives During the COVID-19 pandemic, healthcare professionals are recommended to use PPE to prevent the transmission of disease. Healthcare workers who use N95 FFR, which has an important place, experience complaints such as headache and dizziness. In this study, we plan to find the cause of these complaints and aim to clarify whether they are associated with the use of N95 mask. Method Healthcare workers first put on a surgical mask for at least 1 h and a maximum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 17 publications
1
32
2
1
Order By: Relevance
“…After removing the mask, capillary blood gases were taken and a questionnaire was given. In this study, it was quantitatively shown that the participants’ symptoms were due to respiratory alkalosis and hypocarbia [ 15 ]. The analysis of our study revealed that 1/3 of medical personnel had clearly perceived subjective symptoms, i.e., fatigue or sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…After removing the mask, capillary blood gases were taken and a questionnaire was given. In this study, it was quantitatively shown that the participants’ symptoms were due to respiratory alkalosis and hypocarbia [ 15 ]. The analysis of our study revealed that 1/3 of medical personnel had clearly perceived subjective symptoms, i.e., fatigue or sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies were at high risk of bias (n=18/21) ( 16 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ) primarily due to the potential for recall bias (e.g. use of self-report surveys), participation bias (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies contributed data to the meta-analyses of AEs ( 25 , 30 , 32 , 34 , 36 , 39 , 41 , 42 ), with findings from Zuo, Hua ( 43 ) unable to be statistically combined. Healthcare workers wearing respirators reported more AEs than those wearing surgical masks, specifically: De novo headaches (respirator = 99/159 [62.3%], surgical mask = 156/314 [49.7%]); Respiratory distress or shortness of breath (respirator = 83/148 [56.1%], surgical mask = 52/217 [24.0%]); Facial itching or irritation (respirator = 66/256 [25.8%], surgical mask = 51/256 [19.9%]); Sweating (respirator = 1263/1485 [85.1%], surgical mask = 93/494 [18.8%]); Pressure-related injuries (respirator = 878/1523 [57.6%], surgical mask = 94/532 [17.7%]); and Attention deficit or disorders (respirator = 33/76 [43.4%], surgical mask = 40/145 [27.6%]).…”
Section: Results Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Im Vergleich zu N95-Masken wurden in einer italienischen Studie beim Tragen von chirurgischen MNS-Masken mehr Unbehagen und mehr Beschwerden von den Probanden geäußert [8]. In einer weiteren Studie konnte eine Assoziation zwischen N95-Masken und respiratorischer Alkalose gefunden werden, was u. a. mit Kopfschmerzen, Ängsten, Tremor und Muskelkrämpfen in Zusammenhang steht [9]. Eine ebenfalls unlängst durchgeführte Untersuchung zeigte, dass das Tragen von Gesichtsmasken in Kombination mit Schutzbrillen im klinischen Kontext vermehrt zu Kopfschmerzen führt und dass Mitarbeiter sich hierdurch in ihrer arbeitsbezogenen Leistungsfähigkeit eingeschränkt fühlen [10].…”
Section: Resultsunclassified